Application of Musical Computing to Creating a Dynamic Reconfigurable Multilayered Chamber Orchestra Composition. - Kirke, Alexis (Leonardo Music Journal, 2019)
With increasing virtualization and the recognition that today's virtual computers are faster than hardware computers of 10 years ago, modes of computation are now limited only by the imagination. Pulsed Melodic Affective Processing (PMAP) is an unconventional computation protocol that makes affective computation more human-friendly by making it audible. Data sounds like the emotion it carries. PMAP has been demonstrated in nonmusical applications, e.g. quantum computer entanglement and stock market trading. This article presents a musical application and demonstration of PMAP: a dynamic reconfigurable score for acoustic orchestral performance, in which the orchestra acts as a PMAP half-adder to add two numbers.